Spirulina enhanced the skeletal muscle protein in growing rats - Voltarelli, Fabricio A. [UNESP]; de Mello, Maria Alice R. [UNESP] (Dr Dietrich Steinkopff Verlag, 2008)
Background/Aim of the study This study evaluates the effects of the blue green alga spirulina as the sole dietary source of protein on muscle protein in weaning rats. Methods Young (30 days) Wistar rats were fed, during 60 days, with 17% protein spirulina (S) and compared to rats fed 17% protein casein (C). We evaluated the muscle total protein and DNA contents and the in vitro protein synthesis and degradation rates as well the myosin protein expression. Results The groups presented similar body weight (C = 427.3 +/- 8.6; S = 434.6 +/- 7.7 g) and length (C = 25.4 +/- 0.2; S = 25.6 +/- 0.2 cm). Soleus muscle total protein (C = 2.9 +/- 0.1; S = 2.7 +/- 0.1 mg/100 mg) and DNA (C = 0.084 +/- 0.005; S = 0.074 +/- 0.005 mg/100 mg) contents were also similar in both groups. Protein degradation (C = 427.5 +/- 40.6; S = 476.7 +/- 50.5 pmol/mg(-1) h(-1)) did not differ between the groups but protein synthesis (C = 17.5 +/- 1.0; S = 25.2 +/- 1.9 pmol/mg(-1)h(-1)) and myosin content (western blot analyses) were higher (P < 0.05, t test) in spirulina group. Conclusions Although the spirulina proved adequate protein quality to maintain body growth, the muscle protein synthesis rates were increased by the ingestion of the experimental diet in young rats.
Keywords: skeletal muscle; spirulina; protein